2005
DOI: 10.1021/ie050634k
|View full text |Cite
|
Sign up to set email alerts
|

Dispersion of Floating Solid Particles in Aerated Stirred Tank Reactors:  Minimum Impeller Speeds for Off-Surface and Ultimately Homogeneous Solid Suspension and Solids Concentration Profiles

Abstract: Effects of impeller design, baffle, and gas flow rate on distributions of floating solid particles were examined in a stirred tank of 0.2 m i.d. for solid concentrations up to 50 vol %. Dual small cross-section impeller systems, i.e., dual four-flat blade disk turbines and dual four-pitched blade downflow disk turbines, and large cross-section impellers, i.e., Maxblend impeller and Fullzone impeller, were used. The minimum impeller speeds for off-surface floating-particle suspension decreased with aeration bec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
40
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(40 citation statements)
references
References 26 publications
0
40
0
Order By: Relevance
“…A number of studies focused on three phase systems; among these Nienow et al (1986), Frijlink et al (1990), Micale et al (2000) and Dohi et al (2004) addressed the problem of correlating the agitator speed for complete suspension under gassed conditions. Recently Kuzmanic and Ljubicic (2001), Bao et al (2005) and Tagawa et al (2006), investigated the draw-down of floating solid particles in aerated baffled vessels.…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies focused on three phase systems; among these Nienow et al (1986), Frijlink et al (1990), Micale et al (2000) and Dohi et al (2004) addressed the problem of correlating the agitator speed for complete suspension under gassed conditions. Recently Kuzmanic and Ljubicic (2001), Bao et al (2005) and Tagawa et al (2006), investigated the draw-down of floating solid particles in aerated baffled vessels.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been employed by Takahashi et al (2006) in a boiling liquid system with very good results. Dohi et al (2004) and Tagawa et al (2006) found that Maxblend impeller in transition and turbulent regime is more efficient in terms of energy for solid suspension than multiple turbine systems. In a numerical work, Yao et al (2001) performed a comparison of the dispersive mixing characteristics of Maxblend and double helical ribbons (DHR).…”
Section: Introductionmentioning
confidence: 99%
“…This correlation is not studied because it has not considered influences of volume fraction, particles size, off‐bottom clearance, and so on. Tagawa et al proposed a correlation on the basis of Zwietering method: NCS=sμ0.1(gΔρ/ρl)0.45Xs0.13ds0.2D0.85. …”
Section: Introductionmentioning
confidence: 99%